The Influence of Exposure to Educative Content on Instagram Account @Zeniuseducation on Students' Learning Interest - Gloria Enggelin; Djudjur Luciana Radjagukguk (IJESS International Journal of Education and Social Science, 2023)
There are several findings in research that found that students' interest in learning in Indonesia is currently experiencing a decline during the pandemic, this is due to learning being carried out online. Students have the feeling that online learning is less motivating when compared to classroom learning. The purpose of this study was to find out how much influence exposure to educational content has on the Instagram account @zeniuseducation on students' learning interest. This study uses a quantitative approach. The method used in this study is an explanatory survey method to explain the effect of one variable on another with the help of a research instrument in the form of a questionnaire. The population of this study were followers of the Instagram account @zeniuseducation and the number of samples was drawn based on calculations using the Slovin formula, the results obtained were 100 samples. The sampling technique was carried out by purposive sampling technique. Descriptive analysis found that most of the respondents' educational content exposure variables were in the often exposed category and most of the students' learning interest variables were in the moderate category. The results of the hypothesis test show that the calculated significance value is 0.000 <0.05, which means that there is a significant effect of exposure to educational content on students' learning interest. The magnitude of the influence based on the coefficient of determination test is 43.5%, which means that the remaining 56.5% influence comes from other variables outside this study.